Synthesis, structural characterization and biological activity of 2-(4-methylbenzenesulphonamido)pentanedioic acid amide derivatives: In vitro and in vivo antineoplastic activity (Bangladesh Journal of Pharmacology, 2015)
In the present work few novel 2-(4-methylbenzenesulphonamido)pentanedioic acid amide derivatives and the basic compound 2-(4-methylphenylsulfonamido)pentanedioic acid have been synthesized, characterized and screened for their possible antineoplastic activity both in vitro and in vivo. The in vitro activity was performed against five human cell lines like human breast cancer (MCF-7), leukemia (K-562), ovarian cancer (OVACAR-3), human colon adenocarcinoma (HT-29) and Human kidney carcinoma (A-498). The in vivo activity was performed in female swiss albino mice against Ehrlich ascites carcinoma (EAC). Among the synthesized compounds, ureide, p-bromoanilide, p-nitoanilide, o-bromoanilide and p-methylanilide derivatives of 2-(4-methyl benzene sulphonyl)-pentanedioic acid amides showed encouraging activity in both the in vitro and in vivo compared to other compounds. It was noticed that final derivative compounds show a better activity than the parent compound and it may be due to the substituents present in those compounds.